2006
DOI: 10.1002/ejoc.200600572
|View full text |Cite
|
Sign up to set email alerts
|

Gold Catalysis: Alkylideneoxazolines and ‐oxazoles from Intramolecular Hydroamination of an Alkyne by a Trichloroacetimidate

Abstract: Several propargylic trichloroacetimidates have been prepared and their reactions with gold catalysts studied. Only with the propargyl and the 1‐methylpropargyl substituent was a selective cyclization observed; with gold(III) chloride in acetonitrile only the product of a fast hydroamination to 4‐methylene‐4,5‐dihydrooxazoles was obtained, in chloroform the slower subsequent aromatization could not be prevented which delivered the oxazoles after long reaction times. Up to 3333 turnovers could be reached. With g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(30 citation statements)
references
References 47 publications
1
28
0
1
Order By: Relevance
“…The 6-exo, but not the 5-exo, transformation tolerated substitution at the terminal alkyne carbon atom and both transformations tolerated a range of substitution at the oxygen-bound sp 3 carbon atom. Similar transformations were reported near the same time by Hashmi [11]. Carbamates are also effective nucleophiles for the gold(I)-catalyzed intramolecular hydroamination of alkynes [12].…”
Section: Introductionsupporting
confidence: 55%
“…The 6-exo, but not the 5-exo, transformation tolerated substitution at the terminal alkyne carbon atom and both transformations tolerated a range of substitution at the oxygen-bound sp 3 carbon atom. Similar transformations were reported near the same time by Hashmi [11]. Carbamates are also effective nucleophiles for the gold(I)-catalyzed intramolecular hydroamination of alkynes [12].…”
Section: Introductionsupporting
confidence: 55%
“…18 Recently, Hashmi et al reported an elegant synthesis of halogenated oxazoles via the gold-catalyzed formation of alkylideneoxazolines (path e) 19 followed by the halogenation of them (path f). 18 Such a method have been extended to oxazole synthesis with the introduction of heteroatomic or carbon functional groups 20,21 as well as the further oxidation of iodinated alkylideneoxazolines (path g) 22 by Hashmi's and other groups.…”
Section: -Iodane-mediated Cycloisomerization/functionalization Reactionsmentioning
confidence: 99%
“…In 2009, we found that, in presence of stoichiometric amounts of base, alkylgold(I) complexes could be formed by gold-promoted addition of nitrogen nucleophiles to unactivated alkenes [Eq. (1)]. [6,7] This result led us to posit that generation of an acidic species was important for catalytic turnover in the reported alkene hydroamination reactions.…”
mentioning
confidence: 92%
“…[1,2] While significant progress has been made in the asymmetric hydroamination of allenes, enantioselective goldcatalyzed hydroamination of simple alkenes and dienes has been limited to reactions in which urea is employed as a nucleophile. [3] Furthermore, as simple Brønsted acids are also known to be effective catalysts for alkene hydroamination [4] and gold(I) triflates are often employed in olefin activation, [5] the role of gold in these reactions is unclear.…”
mentioning
confidence: 99%